PERANCANGAN KAPAL INTERCEPTOR SERGAP BERBAHAN HDPE - Budianto; Agung Prasetyo Utomo; Rini Indarti (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
In order to maintain the sovereignty of the unitary state of the Republic of Indonesia, especially in Indonesian waters, reliable and superior defence equipment is required. In general, high-speed boats can manoeuvre with a maximum speed of about 30 to 50 knots. In order to anticipate the condition of high-speed boat manoeuvring, an interceptor vessel is required. Particular attention should be paid to the impact and shock conditions of high-speed manoeuvring. In particular, the construction of the ship’s bow, which is often subject to cracking problems that can cause the ship to sink or the condition of the bow to be destroyed by hitting the reef. Therefore, the interceptor ship must be designed at high speed, taking into account the construction of the bow of the component to ensure strong and safe in operation. The interceptor ship is designed using HDPE, a relatively new type of material for shipbuilding applications with strong and more clayey advantages. For modulus calculations in determining the profile and thickness of the plate on the bow construction of the ship, referring to the high-speed craft regulations. Meanwhile, in order to ensure the strength of the bow structure of the Interceptor ship made of HDPE against the impact load and impact effect, it is necessary to calculate and analyse numerically using the finite element method and to carry out bow structure tests on a laboratory scale, with the results still meeting the allowable stress criteria.